Utilization of Hibiscus Leaves Extract as an Environmentally Friendly Detergent Active Ingredients - Muhamad Aditya Hidayah; Gerda Pintoko Tunjungsari; Alfandi Ahmad; Retno Aliyatul Fikroh (JURNAL SAINS NATURAL, 2022)
Detergent is an ingredient used to maintain cleanliness. In the manufacture of detergents, an active ingredient in the form of LAS (Linear Alkylbenzene Sulfonate) surfactant is often added to kill bacteria. In addition to using synthetic materials, natural ingredients can also be used that can act as antibacterial. One of the natural ingredients with antibacterial activity is hibiscus leaves (Hibiscus tilianceus L). The use of hibiscus leaf extract as a substitute for LAS surfactants aims to reduce the impact of environmental pollution The purpose of this research was to find the right formula in the manufacture of liquid detergent made from hibiscus leaf extract and determine its quality based on SNI 06-0475-1996. The research method used is experimental research that produces qualitative and quantitative data. Qualitative data include phytochemical tests, organoleptic tests, hard water emulsion stability tests, and cleaning power tests. The resulting quantitative data includes the characteristics of the liquid detergent produced based on testing pH, specific gravity, antimicrobial test, phenol coefficient, and levels of active substances. Based on the study, results showed that hibiscus leaf extract contained secondary metabolites in the form of saponins, triterpenoid/steroidal saponins, flavonoids, and polyphenols. The antibacterial test showed that hibiscus leaf liquid detergent had antibacterial activity 1.67 times more effective than phenol. The product test results show that the liquid detergent of hibiscus leaves has the quality according to SNI 06-0475-1996.Keywords: Hibiscus Leaf Extract; Eco-Friendly Detergent; Hibiscus leaves; Surfactant; LAS (Linear Alkylbenzene Sulfonate)